Effect of BaF2 Variation on Spectroscopic Properties of Tm3+ Doped Gallium Tellurite Glasses for Efficient 2.0 μm Laser - Yuan, Jian; Wang, Weichao; Ye, Yichen; Deng, Tingting; Ou, Deqian; Cheng, Junyang; Yuan, Shengjin; Xiao, Peng (Frontiers in Chemistry, 2021)
The effects of substitution of BaF2 for BaO on physical properties and 1.8 μm emission have been systematically investigated to improve spectroscopic properties in Tm3+ doped gallium tellurite glasses for efficient 2.0 µm fiber laser. It is found that refractive index and density gradually decrease with increasing BaF2 content from 0 to 9 mol.%, due to the generation of more non-bridging oxygens. Furthermore, OH− absorption coefficient (αOH) reduces monotonically from 3.4 to 2.2 cm-1 and thus emission intensity near 1.8 μm in gallium tellurite glass with 9 mol.% BaF2 is 1.6 times as large as that without BaF2 while the lifetime becomes 1.7 times as long as the one without BaF2. Relative energy transfer mechanism is proposed. The maximum emission cross section and gain coefficient at around 1.8 μm of gallium tellurite glass glass containing 9 mol.% BaF2 are 8.8×10−21 cm2 and 3.3 cm-1, respectively. These results indicate that Tm3+ doped gallium tellurite glasses containing BaF2 appear to be an excellent host material for efficient 2.0 µm fiber laser development.